Differential prize taxation and structural discrimination in contests - Yosef Mealem; Shmuel Nitzan (Center for Economic Studies and ifo Institute (CESifo), 2012)
This paper evaluates differential prize taxation and structural discrimination as a means of increasing efforts in the most widely studied contests. We establish that a designer who maximizes efforts subject to a balanced-budget constraint prefers dual discrimination, namely, change of the contestants' prize valuations as well as bias of the impact of their efforts. Optimal twofold discrimination is often superior to any single mode of discrimination under any lottery. Surprisingly, in the general N-player contest game, under the prototypical simple lottery, it can yield the maximal possible efforts: the highest valuation of the contested prize. If a single mode of discrimination is allowed, then differential taxation is superior to structural discrimination.
Keywords: D70; D72; D74; D78; 330; contest design; balanced-budget-constraint; differential prize taxation; structural discrimination; dual polarized discrimination; contest success function; lottery; Extensives Spiel; Wettbewerb; Leistungsanreiz; Preisdifferenzierung; Glücksspiel